Indigenous Resurgence Decolonialization and Movements for Environmental Justice - Dhillon, Jaskiran (Berghahn Books, 2022)
From the Standing Rock Sioux Tribe's resistance against the Dakota Access pipeline to the Nepalese Newar community's protest of the Fast Track Road Project, Indigenous peoples around the world are standing up and speaking out against global capitalism to protect the land, water, and air. By reminding us of the fundamental importance of placing Indigenous politics, histories, and ontologies at the center of our social movements, Indigenous Resurgence positions environmental justice within historical, social, political, and economic contexts, exploring the troubling relationship between colonial and environmental violence and reframing climate change and environmental degradation through an anticolonial lens.